Algebraic Hyperstructures and Applications 1991
DOI: 10.1142/9789814539555
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic Hyperstructures and Applications

Abstract: Algebraic Hyperstructures and Applications Downloaded from www.worldscientific.com by UNIVERSITY OF BIRMINGHAM on 08/27/15. For personal use only. ALGEBRAIC HYPER�RU�URESAND APPLICATIONS Algebraic Hyperstructures and Applications Downloaded from www.worldscientific.com by UNIVERSITY OF BIRMINGHAM on 08/27/15. For personal use only. This page is intentionally left blank Algebraic Hyperstructures and Applications Downloaded from www.worldscientific.com by UNIVERSITY OF BIRMINGHAM on 08/27/15. For personal use on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 6 publications
0
79
0
Order By: Relevance
“…As it is well known [12], a hyperstructure is a non-empty set H together with a map · : H × H → P * (H), called a hyperoperation, where P * (H) is the family of all non-empty subsets of H. The image of pair (x, y) is denoted by x · y. If x ∈ H and A, B ⊆ H, then by A · B, A · x and x · B we mean…”
Section: Preliminariesmentioning
confidence: 93%
See 1 more Smart Citation
“…As it is well known [12], a hyperstructure is a non-empty set H together with a map · : H × H → P * (H), called a hyperoperation, where P * (H) is the family of all non-empty subsets of H. The image of pair (x, y) is denoted by x · y. If x ∈ H and A, B ⊆ H, then by A · B, A · x and x · B we mean…”
Section: Preliminariesmentioning
confidence: 93%
“…Hypersructures have many applications to several branches of both pure and applied sciences (see for example [4] and [5]). Vougiouklis [12,10] introduced a new class of hyperstructures called now H v -structures, and Davvaz [7] surveyed the theory of H v -structures. After the introduction of fuzzy sets by Zadeh [14], there have been a number of generalizations of this fundamental concept.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, people have observed that hyperstructures have many applications to several branches of both pure and applied sciences (see [2][3][4][5]). In particular, a semihypergroup is the simplest algebraic hyperstructure which possess the properties of closure and associativity.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperstructure theory and its applications have been investigated by the contribution of many mathematicians. The principal notions of hyperstructure theory can be found in [9,10,11,12,14,29].…”
Section: Introductionmentioning
confidence: 99%